Relationships Matter Most: A Mixed Methods Study into Meaning in Life in Personality Disorder, Before and After Treatment - Angelien Steen; Pauline Sam; Carmen Schuhmann; Arjan W. Braam (Religions, 2025)
Meaning in life is often at stake in patients with personality disorder (PD) and associated with a lack of self-direction. Meaning in life, including religion and spirituality, seems to contain facets within personality and facets independent of personality and might change during treatment. The sample included patients with PD (pre-treatment n = 125, post-treatment n = 85) and a control group (n = 69). To clarify (changes in) facets of meaning in life, open interview questions on meaning, meaninglessness, recovery, and supportive resources were subjected to a qualitative and quantitative analysis. The results show that significant others are the primary, most important source of meaning in life and support for PD patients and controls. Negative feelings, feelings of loss, and a psychiatric disorder are the three most frequent “causes” of meaninglessness in patients, stressing the importance of therapy to treat these issues. In the PD group, pets are a relevant source of meaning in life. Treatment is likely to contribute to the restoration of meaning in life. Here, addressing interpersonal functioning represents a key element, probably by improving connectedness with loved ones.